Introduction and Analysis of Exoplanet Detection Techniques - Zhao, Xiaoxi (Transactions on Computer Science and Intelligent Systems Research, 2024)
The exoplanet study is important for exploring life’s origins in the universe. With the development of astronomical observation technology, more and more exoplanets have been discovered, and the exploration of habitable planets and the study of planetary atmospheres have become focal areas of study. In this paper, the transit and radial velocity methods for finding exoplanets are introduced and analysed in detail, by introducing the principles of these two methods and showing the calculation progress with specific planetary data. As a result, the parameters of exoplanet can be derived from the principle of doppler effect and binary system. Each method has its advantages and limitations. For radial velocity method, its limitation is that low-mass orbiting planets (planets with mass less than 10 ) cannot be detected because those planets cannot cause detectable and measurable transit signals. Also cannot be directly measured through the radial velocity method unless the value of inclination is obtained. For the transit method, to get full information and confirm the existence of the planet, complementary measurement is needed, such as radial velocity. Another limitation is the instability of observations. There is a maximum range of the inclination that can observe the transit on the star and nebulae in the universe may block the observing sight, both lead to a limit probability of finding the planet’s transit. So, the complementarity between the methods can make the results more comprehensive and precise. From these, it is possible to find more habitable terrestrial planets.